PENGARUH KEMAMPUAN PROFESIONAL GURU TERHADAP MUTU PEMBELAJARAN PESERTA DIDIK - Ghiffarin Kintan Arini (Universitas Pendidikan Indonesia, 2021)
The purpose of this research is to determine the influence of teachers professional competence on student’s learning quality at SMKN 1 Bandung. The background of this research is problems based on an interview conducted to teachers of SMK Negeri 1 Bandung, teachers discovered that there are students who are not actively participated during the process of learning and some who have not met the minimum completion score which has been determined. Therefore, this study will describe the student’s learning quality, the teachers professional competence, and to determine whether there is simultaneous influence of teachers professional competence on student’s learning quality. This research applies descriptional method with quantitative approach. Results shows that on the variable of teachers professional ability on dimension developing professionalism on an ongoing basis by performing reflective actions got the lowest score (4,36) compared to other dimension. Another result from this research shows that on variable student’s learning quality on learning outcomes dimension got the lowest score (4,39) in comparation to other dimension. The analysis result from this research initiate that in general, both teachers professional competence and student’s learning quality in SMK Negeri 1 Bandung scored excellence and there is a significant influence between teachers professional competence and student’s learning quality. Thereupon, based on the result it is recommended for the school to frequently hold traning and education, In House Training, Teachers’ Working Forum (MGMP) and self-evaluation also to contemplate or even escalate every factors that can influence the learning outcomes so the students can improve capability, knowledge, and skills.